Status quo bias and the number of alternatives: An empirical illustration from the mutual fund industry - Alexander Kempf; Stefan Ruenzi (University of Cologne, Centre for Financial Research (CFR), 2005)
We examine the extent of the Status Quo Bias (SQB) in a real-world repeated decision situation. Individuals who are subject to a SQB tend to choose an alternative that was chosen previously (i.e. their status quo), even if it is not the optimal choice any more. We examine the US equity mutual fund market and find strong evidence for the existence of a SQB in this market. Furthermore, the SQB is more severe in segments where there are more funds to choose from. Thereby, we deliver the first empirical confirmation of the experimental result of Samuelson and Zeckhauser (1988), that the SQB positively depends on the number of alternatives.
Keywords: G20; G23; 330; Status Quo Bias; Mutual Funds; Number of Alternatives; Performance Flow Relationship